WARNABALI: BALINESE COLOR INTENSITY DIVERSIFICATION FOR DEVELOPMENT OF BALI MODERN INTERIOR AND ARCHITECTURE COATING IN ADDITIVE COLOR ONLINE BASED EXPERIMENT - Anak Agung Gede Rai Remawa; I Kadek Dwi Noorwatha; I Made Pande Artadi; Toddy Hendrawan Yupardhi; Putu Ari Darmastuti (Journal of Aesthetics, Design, and Art Management, 2022)
Purpose: This study aims to conduct experiments on enriching the intensity of traditional Balinese colors that are relevant to the application of color in modern interiors and architecture. Research methods:The research method uses online-based experiments by mixing Balinese colors with light and dark characters in a ratio of 66.7%: 33.3%. Mixing is done by crossing process and the results of the cross process are arranged into a Balinese color palette based on Additive Colors. Findings:The color cross method with a ratio of 66.7% light to 33.3% dark produces bali color variants with various tint intensities. The scan results on the Balinese print-based color composition arranged in the nawa sangha cosmology, which is processed online through the dopely.top website, produces relevant colors developed in modern interiors and architecture. The process of diversifying the color intensity will provide recommendations for its application to residential and non-residential interiors. Implications: Provide insight into the use of traditional Balinese colors to designers and architects, in an effort to preserve and strengthen tradition-based knowledge for the development of modern design science.